RESTATEMENT TENTANG YURIDIKSI PERADILAN MENGADILI PERBUATAN MELAWAN HUKUM PEMERINTAH (RESTATEMENT ON JUDICIAL JURISDICTION IN ADMINISTRATIVE TORT) - Enrico Parulian Simanjuntak (Faculty of Law, Universitas Diponegoro, 2019)
One of the crucial problems after enactment of Government Administration Act (UUAP) concerns the extent to which the scope of court jurisdiction relating administrative torts (onrechtmatige overheidsdaad) or OOD, as intended in Article 1365 of the Civil Code. There are at least two different views on the issue. First, administrative court mutatis mutandis has power to resolve the case relating onrechtmatige overheidsdaad, this view is represented by Supreme Court Circular or Surat Edaran Mahkamah Agung (SEMA) No. 4/2016. A different view holds that the OOD act is a genus whereas the factual act as referred to UUAP is a species. This second view is not mutatis mutandis totally transferring the authority of civil judges to administrative court try the OOD case. This difference of opinion is important to be studied more thoroughly in order to know the real issue of the different views.